Are solvent effects important for intramolecular C—H···O− hydrogen bonding interactions?. (11th November 2018) - Wang, Jinhu; Shao, Linjun; Yan, Peng; Liu, Chunli; Liu, Xuejing; Zhang, Xian M.
Abstract: Oxygen atoms are located at the center of the symmetrical rectangles formed by four ortho t‐ butyl carbon‐hydrogen (C—H) bonds for the conformational inflexible 2, 6‐di‐ t ‐butyl‐4‐substituted phenoxide anions, in which the nonbonded O···H and O···C distances are all significantly shorter than sums of the related van der Waals' radii. Noncovalent interaction (NCI) and atoms in molecules (AIM) analysis reveal that the oxygen atom can form four equivalent intramolecular C—H···O − hydrogen bonds (approximately 3.0 kcal/mol) regardless of size and polarity of the para‐substituents, implying that each phenoxide anion is stabilized by approximately 12 kcal/mol C—H···O − hydrogen bonding interaction. The C—H···O − hydrogen bonding stabilizations are strongly supported by acidity augmentation of approximately 1.6 p K units (approximately 40 times) for introduction of two bulky t ‐butyl groups into the ortho positions of 4‐substituted phenols (G = H, Me, t ‐Bu, MeO, and NO2 ) in dimethyl sulfoxide solution. Furthermore, solvents with largely varying polarity show negligible effects on the intramolecular C—H···O − hydrogen bonding strengths. Abstract : There are four C—H···O − hydrogen bonds in each 2, 6‐di‐ t ‐butyl‐4‐substituted phenoxide anions. Solvents have negligible effects on these hydrogen bonding interactions.